Health care reform and disparities : history, hype, and hope - Miles, Toni P. (Santa Barbara, Calif. : Praeger, 2012)
"This book exposes and examines how Medicare, Medicaid, and private health insurance plans combined with widespread business practices and fraud create inequity the root cause of our dysfunctional health care system, and the reason for the rising cost of health care for all Americans"--Provided by publisher.
Introduction: how to approach the problem of health disparities and health care reform -- Overview : Diminishing health disparities -- Beyond Medicaid -- Quality, disparities, and Title III -- Business models, disparities, and reform -- Lobbyists, advocates, and disparity -- Health care fraud -- Young adults -- Correctable disparities, the Affordable Care Act, and public health research.
Includes bibliographical references and index.
Keywords: Health care reform -- United States; Health insurance -- United States; Discrimination in medical care -- United States; Health services accessibility -- United States; Healthcare Disparities -- United States; Health Care Reform -- United States; Insurance, Health -- United States